Improving system performance using microgrid energy storage systems - Yang, Kewen (2017)
The power disturbances happen frequently in the Microgrid system. To prevent the power disturbances, ESS system with controllers can be applied. In this project, the main focus is to study and develop different solutions to reduce the effect by power disturbance and improve the Microgrid performance. There are four types of ESS control schemes that have been discussed. ESS supplied DVR system to mitigate voltage sag/swell; ESS supplied active power system to improve power factor; ESS system controlled peak demand shaving/levelling; ESS system controlled emergency power supply. All these four cases are simulated and analyzed in MATLAB Simulink platform successfully. Based on the results, the power disturbances are prevented or reduced dramatically.